Social welfare and individual responsibility - Schmidtz, David; Goodin, Robert E. (Cambridge : Cambridge University Press, 1998)
The issue of social welfare and individual responsibility has become a topic of international public debate in recent years as politicians around the world now question the legitimacy of state-funded welfare systems. David Schmidtz and Robert Goodin debate the ethical merits of individual versus collective responsibility for welfare. David Schmidtz argues that social welfare policy should prepare people for responsible adulthood rather than try to make that unnecessary. Robert Goodin argues against the individualization of welfare policy and expounds the virtues of collective responsibility.
Title from publisher's bibliographic system (viewed on 05 Oct 2015).
Keywords: elektronické knihy; electronic books; Social justice; Responsibility; Social policy -- Moral and ethical aspects; Public welfare -- Moral and ethical aspects; Welfare state -- Moral and ethical aspects